Quebec French – the Struggle for National Identity - Bobowska-Nastarzewska, Patrycja (SORUS S.C. Wydawnictwo i Drukarnia Cyfrowa, 2009)
This paper addresses an issue of “linguistic human rights”. The author discusses the endeavours of the inhabitants of Quebec to gain independence as well as their struggle for their language and identity. First, the paper focuses on the process of gaining independence for the Quebecois on the historical and social planes. Then, the author introduces the notion of bilingualism in Canada and goes on to examine the Quebecois language. Specific linguistic examples are presented providing convincing evidence that the language used by the Quebecois constitutes an original variety of French. The final part of the paper examines the role of literature in the process of the development of the Quebecois national identity.

(Język quebecki – walka o tożsamość narodową). Autorka prezentuje dążenie mieszkańców Quebecu do niepodległości, któremu towarzyszy walka o tożsamość narodową i prawo do własnego języka. Na wstępie skupia się na procesie kształtowania się niepodległości Quebecczyków na płaszczyźnie historycznej i społecznej. Następnie rozpatruje zagadnienie bilingwizmu w Kanadzie i zajmuje się językiem quebeckim, podając konkretne przykłady językowe poświadczające istnienie oryginalnej odmiany języka francuskiego, którą posługują się Quebecczycy, oraz ilustrujące stosunek mieszkańców Quebecu do języka angielskiego. Autorka podkreśla również rolę literatury w procesie kształtowania się tożsamości narodowej Quebecczyków.
Keywords: Quebec French; linguistic human rights; język quebecki; Quebec; bilingualism